A Case Study Of SOHU - Kui, Zhang Wen (2005)
This study describes Sohu's background and history, organizational structure, products and service, HR management, competitors and its overall performance throughout its establishment. Nevertheless, Sohu also faces some problems such as users' loss due to violation and a large risk from loans.